Fine particulate air pollution and adult hospital admissions in 200 Chinese cities: a time-series analysis. (3rd June 2019) - Tian, Yaohua; Liu, Hui; Liang, Tianlang; Xiang, Xiao; Li, Man; Juan, Juan; Song, Jing; Cao, Yaying; Wang, Xiaowen; Chen, Libo; Wei, Chen; Gao, Pei; et al.
Abstract: Background: The association between short-term exposure to ambient fine particulate matter (PM2.5 ) and morbidity risk in developing countries is not fully understood. We conducted a nationwide time-series study to estimate the short-term effect of PM2.5 on hospital admissions in Chinese adults. Methods: Daily counts of hospital admissions for 2014–16 were obtained from the National Urban Employee Basic Medical Insurance database. We identified more than 58 million hospitalizations from 0.28 billion insured persons in 200 Chinese cities for subjects aged 18 years or older. Generalized additive models with quasi-Poisson regression were applied to examine city-specific associations of PM2.5 concentrations with hospital admissions. National-average estimates of the association were obtained from a random-effects meta-analysis. We also investigated potential effect modifiers, such as age, sex, temperature and relative humidity. Results: An increase of 10 μg/m 3 in same-day PM2.5 concentrations was positively associated with a 0.19% (95% confidence interval: 0.07–0.30) increase in the daily number of hospital admissions at the national level. PM2.5 exposure remained positively associated with hospital admissions on days when the daily concentrations met the current Chinese Ambient Air Quality Standards (75 μg/m 3 ). Estimates of admission varied across cities and increased in cities with lower PM2.5 concentrations ( p = 0.044) or higher temperatures ( p = 0.002) and relative humidity ( p = 0.003). The elderly were more sensitive to PM2.5 exposure ( p < 0.001). Conclusions: Short-term exposure to PM2.5 was positively associated with adult hospital admissions in China, even at levels below current Chinese Ambient Air Quality Standards.